Upaya Food & Beverage Restaurant Dalam Meningkatkan Kepuasan Tamu Melalui Variasi Product - Hesty Woro Yusnita dan Atun Yulianto (Universitas Bina Sarana Informatika, 2013)
The development of the tourism industry today is very significantly as with the development of economic, social, technological and tourism business. This condition is also crucial in affect the development of the food and beverage industry that a very important role in the tourism business. Kedai 24 is a business engaged in the field of food and beverage that offers a menu with a wide variation in quality and good service to improve guest satisfaction. Writers interested in this topic so do some research to determine the extent of the role of food & beverage Kedai 24 in the produce variety of products for guest satisfaction by using descriptive qualitative research methods. Research results show that it food & beverage roles in providing products for guest satisfaction is determined by variations in the resulting menu and the quality of services provided by the waiter/waitress Kedai 24. While guest satisfaction can be improved through a more pleasant working atmosphere and good communication between the inside of the restaurant serving guests in order to create a conducive working environment. Keyword : Food and beverage, product, guest satisfaction